2017
DOI: 10.1016/bs.mie.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the Development of In Silico GPCR Models

Abstract: The Reggio group has constructed computer models of the inactive and G-protein activated states of the cannabinoid CB1 and CB2 receptors, as well, several orphan receptors that recognize a sub-set of cannabinoid compounds, including GPR55 and GPR18. These models have been used to design ligands, mutations and covalent labeling studies. The resultant second generation models have been used to design ligands with improved affinity, efficacy and sub-type selectivity. Herein, we provide a guide for the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 112 publications
(172 reference statements)
1
16
0
Order By: Relevance
“…Our collaborators, Morales et al [3] have recently developed an in silico model of GPR3. In developing the model, they hope to gain insight into the structure and function of GPR3 and use the model as a powerful tool for the development of high-affinity/ potency ligands for the receptor.…”
Section: Significance and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our collaborators, Morales et al [3] have recently developed an in silico model of GPR3. In developing the model, they hope to gain insight into the structure and function of GPR3 and use the model as a powerful tool for the development of high-affinity/ potency ligands for the receptor.…”
Section: Significance and Implicationsmentioning
confidence: 99%
“…These three receptors share approximately 60% amino acid identity [1]. They are also phylogenetically related to the spingosine-1-phosphate (S1P) receptor, lysophosphatidic acid receptor, melanocortin receptor, and cannabinoid receptors [2,3]. Despite being related, the similarity of GPR3, GPR6, and GPR12 to other receptor groups is not sufficient to suggest a common ligand.…”
Section: Introductionmentioning
confidence: 99%
“…GPR3, GPR6 and GPR12 also contain highly conserved residues in the transmembrane helices such as N1.50, D2.50, R3.50, W4.50, P6.50, and P7.50. In addition, they preserve the specific motifs present in TMH3, TMH6 and TMH7 which are DRY, CWXP, and NPXXY motifs, respectively (Morales et al 2017a). …”
Section: General Features: Structure and Expressionmentioning
confidence: 99%
“…Although no crystal structure has been reported yet for any of these orphan receptors, computational molecular models are being developed based on GPCRs with currently available crystal structures (Morales et al 2017a). These homology models take into consideration structural differences and similarities with other GPCRs while identifying potential binding pocket residues for GPR3, GPR6 and GPR12.…”
Section: General Features: Structure and Expressionmentioning
confidence: 99%
“…The IC conformational changes due to the β-arrestin activation mechanism are not fully elucidated and studied as G-protein activation among GPCRs. It has been suggested that conformational changes occur in TMH7-Hx8 domains accompanying β-arrestin signaling [49,50], with no changes in the conformational status of TMH3/TMH6, keeping the ionic lock intact.…”
Section: Ionic Lock and Toggle Switchmentioning
confidence: 99%